Anxiety and depression in adolescents with a visible difference: A systematic review and meta-analysis. (June 2020) - van Dalen, M.; Dierckx, B.; Pasmans, S.G.M.A.; Aendekerk, E.W.C.; Mathijssen, I.M.J.; Koudstaal, M.J.; Timman, R.; Williamson, H.; Hillegers, M.H.J.; Utens, E.M.W.J.; Okkerse, J.M.E.
Highlights: A meta-analysis was executed with 11 articles to assess depression and anxiety. Adolescents with a visible difference experience more anxiety than unaffected peers. No significant effects were found for symptoms of depression. Abstract: Living with a visible difference can entail challenging social situations, associated with psychosocial symptoms. However, it is not clear whether adolescents with a visible difference experience more anxiety and depression than unaffected peers. We aim to determine whether adolescents with a visible difference experience more symptoms of anxiety and depression than unaffected peers. A literature search was conducted in Embase, Medline Ovid, Web of Science, Cochrane CENTRAL, PsycINFO Ovid, and Google Scholar. Meta-analyses were done using random-effects models to calculate a standardised mean difference. Analyses for subgroups were used to study causes of visible difference. Eleven studies were identified ( n = 1075, weighted mean age = 15.80). Compared to unaffected peers, adolescents with a visible difference experience more symptoms of anxiety (SMD = 0.253, 95 % CI [0.024, 0.482], p = .030), but not depression (SMD = 0.236, 95 % CI [−0.126, 0.599], p = .202). Adolescents with a skin condition did not experience more symptoms of anxiety (SMD = 0.149, 95 % CI [−0.070, 0.369], p = .182) or depression (SMD = 0.090, 95 % CI [−0.082, 0.262], p = .305) when compared to unaffected peers. Overall, more symptoms of anxiety are found in adolescents with a visible difference compared to peers. No differences in anxiety or depression were found for skin differences. Screening for anxiety is recommended.